BUDGETARY PROVISION OF REPATRIATION WITHIN THE SYSTEM OF MARKETING DECISIONS OF SERVICE SECTOR ENTERPRISES CONSIDERING PRODUCT STRATEGY - Mishchuk, Ievgeniia; Korolenko, Rita (Current Problems of Sustainable Development, 2026)
The article elaborates the conceptual foundations of the interaction between budgetary provision for repatriation at the state level and the product policy of service sector enterprises, which form an integrated complementary system combining financial incentives and market mechanisms. It is demonstrated that the effectiveness of such a system is determined by the degree of synchronization between  state priorities and business strategic orientations, which ensures not only the attraction of repatriates but also the maximization of their economic contribution to the national economy. It is emphasized that market actors, particularly business entities, act as institutional intermediaries between state incentives and the real labor market, generating through innovation-oriented development of the service sector new jobs adapted to the professional and intellectual potential of repatriates. It is established that the impact of repatriation processes necessitates the transformation of product strategies of service sector enterprises, manifested in the expansion of service assortments, improvement of quality standards, digitalization of service processes, and deeper customer segmentation. As a result, a more complex and higher-quality market offering structure is formed, contributing to increased business competitiveness and an expanded tax base through higher volumes of service sales. It is shown that repatriates may simultaneously act as both consumers and active entrepreneurial agents, creating new business units in the service sector. It is substantiated that marketing decisions in the sphere of product strategy of service enterprises are shaped by internal determinants and external factors. A comprehensive analysis of economic activity ensures the systemic coherence of managerial decisions, enhances the efficiency of innovation and labor capital utilization. Directions of interconnection between state budget expenditures and the potential level of repatriate involvement in economic activity within the service sector are identified. This makes it possible to assess the degree of institutional readiness of public policy conditions for mass, moderate, or targeted integration of repatriates into the labor market.
Keywords: analysis of economic activity; budget; government spending; competencies; marketing solutions; services; product strategy